2010
DOI: 10.1080/01496390903423550
|View full text |Cite
|
Sign up to set email alerts
|

Chloromethylated Activated Carbon: A Useful New Synthon for Making a Novel Class of Sorbents for Heavy Metal Separations

Abstract: The chloromethylation of activated carbon is described. Chloromethylation was found to produce a carbon derivative with a surface area of 1310 m2/g and no significant change in the pore structure. The product was found to contain ~1.5 mmole of –CH2Cl groups per g of material, similar to the functional density reported in the original Merrifield resin synthesis. Displacement of the benzylic chloride was achieved by treating this material with an excess of sodium thiosulfate in refluxing aqueous methanol. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…Previous work has shown that thiol-SAMMS has a high affinity for Hg, Cd, and Pb in natural waters, with K d values in excess of 10 4 and occasionally exceeding 10 6 (81). Inspection of the data in Table 4 shows that K d values are smaller in biological matrices than in natural waters.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that thiol-SAMMS has a high affinity for Hg, Cd, and Pb in natural waters, with K d values in excess of 10 4 and occasionally exceeding 10 6 (81). Inspection of the data in Table 4 shows that K d values are smaller in biological matrices than in natural waters.…”
Section: Resultsmentioning
confidence: 99%
“…Görüldüğü gibi sayısız çoklukta madde sentezlenebilir ve katı faz özütleyici olarak kullanılabilir [38]…”
Section: Katı Faz öZütleme Yöntemiunclassified
“…Görüldüğü gibi sayısız çoklukta madde sentezlenebilir ve katı faz özütleyici olarak kullanılabilir [38]. Son yıllarda katı faz özütleyici olarak nano boyuttaki katı malzemeler iyi tanecik boyutu ve kimyasal aktiviteleri gibi gelişmiş kendine özgü özellikleri nedeniyle giderek artan bir önem kazanmaktadır.…”
Section: Katı Faz öZütleme Yöntemiunclassified
“…However, these chelation agents still have many disadvantages and low efficacy. They are also not effective in removing Cd and toxic anions such as chromate and arsenate [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%